Biological monitoring of Persistent Organic Pollutants in human milk in Israel. (October 2015) - Wasser, Janice; Berman, Tamar; Lerner-Geva, Liat; Grotto, Itamar; Rubin, Lisa
Highlights: Levels of POPs exposure in Israel have declined significantly in the last 30 years. For POPs found at detectable levels in Israel, most were lower than reported in Europe. Aldrin, endrin, and mirex were not found at detectable levels in the pooled sample. Baseline measures were established for dioxins and furans in human milk for Israel. Abstract: Background: The Stockholm Convention on Persistent Organic Pollutants (POPs) aims to eliminate or restrict the production and use of POPs around the globe. The Ministry of Health, collaborating with the Ministry of Environmental Protection, measured the exposure of the population to POPs as part of the WHO-coordinated exposure study. Human milk, with a relatively high fat content is a preferred matrix for the monitoring of exposure. Methods: Donors of breast milk were recruited from three hospitals after signing informed consent forms. Breast milk was collected from 52 primipara women, aged 23-35, living in Israel for the last 10 years who gave birth to singleton full term healthy infants. Samples, collected at 3-17 weeks postpartum, were stored at -20 °C until sent to the WHO Reference Laboratory, State Laboratory for Chemical and Veterinary Analysis of Food (CVUA), in Frieburg, Germany for a single pooled analysis. Mothers were provided with the pooled analysis results. Results: Out of over 50 Persistent Organic Pollutants listed in the analysis, 16, including aldrin, endrin, parlar and mirex were not found at detectable levels in the Israeli pooled sample. For the indicator compounds found at detectable levels, most were lower than those reported in European countries. Discussion: Since 1982, levels of POPs contamination as measured in breast milk have declined significantly. This is likely due to restrictions on agricultural, industrial, and other uses of many POPs in Israel. Ongoing biomonitoring in Israel and inter-ministerial collaboration supports the elimination of POPs in the environment and human milk.